Assignment Computations Based on Cexp Average in Various Ladder Graphs - A.Rajesh Kannan; P. Manivannan; K. Loganathan; K. Prabu; Sonam Gyeltshen (Journal of Mathematics)
This study introduces the Cexp average assignments and investigates its properties using various ladder graphs. The ladder graphs can be found in every communication networks. Ladder networks are increasingly being used in everyday life for monitoring and environmental applications such as domestic, military, surveillance, industrial, medical applications, and traffic management. These datasets are afflicted by the average representation of the graph structure. It aids in the visualisation and comprehension of data analysis. The Cexp labeling is used in sensor networks, adhoc networks, and other applications. It also efficiently creates a communication network after using noise reduction methods to remove salt and pepper noise.